Shadow education: patterns and scale of private supplementary tutoring in English in secondary education at urban Dhaka in Bangladesh - Mahmud, Rafsan; Kenayathulla, Husaina Banu (Taylor & Francis, 2018)
Private supplementary tutoring with an additional fee is generally called shadow education, and this has become a common phenomenon in urban Dhaka, where patterns and scale of tutoring in English have been remarkable in recent years. This study used a mixed-methods approach that included quantitative and qualitative data collected from a survey and individual interview. Tutoring in English has been a regular feature of the teaching profession in this urban area. The paper examines various patterns of private tutoring in English and focuses on the amount of tutoring, including the tutoring received and not received by students in urban Dhaka. It shows the variations of scale regarding tutoring in English between male and female students. The study also identifies different types of private tutors who deliver supplementary tutoring. Finally, the choices pupils make regarding their evaluation on the effectiveness of shapes of tutoring in English are discussed.